The prostatic urethral angle can predict the response to alpha adrenoceptor antagonist monotherapy for treating nocturia in men with lower urinary tract symptom: A multicenter study - Kim, Byung Hoon (Prostate Int, 2016)
BACKGROUND: We evaluated ultrasonography variables associated with the improvement of nocturia after administration of alpha adrenoceptor antagonist (alpha blocker) monotherapy. METHODS: From February to October 2014, 679 men with lower urinary tract symptoms (LUTS) underwent ultrasonography including prostate volume, transitional zone volume, prostatic urethral length, the ratio between prostatic urethral length and prostate volume (RPUL), intravesical prostatic protrusion (IPP), and prostatic urethral angle (PUA). Among them, 108 men who had pre-treatment nocturia without nocturnal polyuria (nocturnal polyuria index < 33%) and were treated with alpha blocker monotherapy over 3 months were enrolled. Patients were divided into the improved (< 2 times of nocturia) and non-improved group (more than 2 times) after administration of alpha blockers. Along with ultrasonography, international prostate symptom score (IPSS) and uroflowmetry was assessed. RESULTS: After alpha blocker treatment, 25.0% of patients (27/108) showed improvement of nocturia. These patients were significantly younger (59.6 vs 68.0 years, P = < 0.001) with lower PUA (31.8 vs. 39.4°, P = 0.009) compared with the non-improved group. In ROC analysis, the area under the curve using the PUA was 0.653 (95% CI = 0.532–0.774, P = 0.018). Using 33.5° as a cut-off level, the sensitivity and specificity for predicting the improvement of nocturia after medication reached 67.9% and 55.6%, respectively. Patients with lower PUA (PUA < 33.5°) had more improvement of nocturia (36.6 vs. 17.9%, P = 0.030), lower IPSS score (14.2 vs. 18.3, P = 0.005), and better quality of life index (3.1 vs 3.8, P = 0.021). CONCLUSIONS: In the patients with lower PUA (particularly lower than 33.5°), nocturia was improved by administration of alpha blocker monotherapy.